2021
DOI: 10.1002/bdr2.1896
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis in Ontario, Canada: 2012–2018

Abstract: Background Gastroschisis is a congenital anomaly of the abdomen in which the intestines are found outside of the body at birth. While no clear causative factors have been identified, it is strongly associated with young maternal age. Other reported associations include low maternal socioeconomic status, low maternal body mass index (BMI), and smoking. Methods This is a retrospective review of epidemiologic data relating to cases of gastroschisis in Ontario from 2012‐2018 in the Better Outcomes Registry & Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
1
12
0
5
Order By: Relevance
“…42 An Ontario study (2012-2018) reported no trend. 43 Neither study included early fetal deaths or terminations. 42,43 Additional social risk factors include maternal smoking, use of marijuana, illicit drugs and alcohol, low BMI, poor nutrition and socioeconomic disadvantage.…”
Section: Gastroschisismentioning
confidence: 99%
See 1 more Smart Citation
“…42 An Ontario study (2012-2018) reported no trend. 43 Neither study included early fetal deaths or terminations. 42,43 Additional social risk factors include maternal smoking, use of marijuana, illicit drugs and alcohol, low BMI, poor nutrition and socioeconomic disadvantage.…”
Section: Gastroschisismentioning
confidence: 99%
“…43 Neither study included early fetal deaths or terminations. 42,43 Additional social risk factors include maternal smoking, use of marijuana, illicit drugs and alcohol, low BMI, poor nutrition and socioeconomic disadvantage. 43 There are fewer exposures to many of these risk factors in the Hutterite population, where there were no cases of gastroschisis between 1980 and 2016.…”
Section: Gastroschisismentioning
confidence: 99%
“…Maternal health and behavioral data were not available in the SINASC database. Therefore, we could not evaluate factors quoted as related to gastroschisis, such as body mass index (Benjamin, Ethen, Canfield, & Mitchell, 2020; Bourque et al, 2020); tobacco, alcohol, and illicit drugs use (Bourque et al, 2020); sexually transmitted infections and urinary tract infections (Baer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal body mass index (BMI) was not available for our study, but data from Canada, United Kingdom and United States associate low pre‐pregnancy BMI and maternal age <20 years with increased risk of gastroschisis, which may suggest an etiological role related to biological immaturity (Bourque et al, 2020; Hale et al, 2017; Siega‐Riz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the evidence is mixed and mostly limited to ecological studies. A more recent study, also using data from BORN Ontario for 2012 to 2018 found positive associations between maternal cannabis use and gastroschisis [ 28 ]. Additionally, there is evidence for the development of ventricular septal heart defects, esophageal atresia and diaphragmatic hernia [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%